Effects of Online Psychological Crisis Intervention for Frontline Nurses in COVID-19 Pandemic - He, Chunyan; Chang, Shuying; Lu, Ying; Zhang, Hongmei; Zhou, Haining; Guo, Yunfei; Gao, Bu-Lang (Frontiers in Psychiatry, 2022)
\Objective: The psychological problems of frontline nurses in COVID-19 prevention and control are very prominent, and targeted intervention is needed to alleviate them. This study was to assess the impact of online intervention programs on psychological crisis of anxiety, depression levels and physical symptoms among frontline nurses fighting the COVID-19 pandemic. Methods: A three-stage online psychological crisis intervention program was established. The General Anxiety 7 (GAD-7) assessment, Patient Health Questionnaire-9 (PHQ-9), and the Self-rating Somatic Symptom Scale (SSS) were used to evaluate the effect of intervention on the day before entering isolation wards (Time 1), the first day after leaving the isolation ward (Time 2), and at the end of the intervention (Time 3). Results: Sixty-two nurses completed the study, including 59 female (95.2%) and three male nurses (4.8%) with an age range of 23-49 (mean 33.37 ± 6.01). A significant (P<0.01) difference existed in the scores of GAD-7, PHQ-9, and SSS at different intervention periods. The GAD-7 score was significantly (P<0.001) lower at the end of quarantine period (time 3) than that before entering the isolation wards (time 1) or after leaving the isolation wards (time 2), the PHQ-9 score was significantly (P = 0.016) lower at the end of quarantine period (time 3) than that after leaving the isolation wards (time 2), and the SSS score was significantly (P <0.001) lower at the end of quarantine period (time 3) than that before entering the isolation wards (time 1) or after leaving the isolation wards (time 2). Conclusion: The three-stage online intervention program based on the psychological crisis can be effective in reducing negative emotions and somatic symptoms and improving the mental health of frontline nurses in prevention and control of the COVID-19 epidemic. It may provide an empirical basis for psychological crisis intervention of frontline medical staff when facing public health emergencies.